“Como é no seu país?” Estudo autoetnográfico de uma prática pedagógica em Português Língua de Acolhimento para mulheres migrantes no Brasil: implicações para a formação de professores - Bottura, Eleonora Bambozzi (Universidade Federal de São Carlos, 2019)
This doctoral thesis consists of an autoethnographic doing and writing of my lived experiences as a teacher of Portuguese Welcoming Language (PWLg) in an exclusive course for vulnerable immigrant and refugee women in Brazil. The choice for the methodological approach derives from the inevitable and necessary outcome of my practice as a teacher and researcher. Teaching PWLg is linked directly to the context of contemporary migrations and it is constituted by strong social, humanitarian and political functions, aiming at the integration of migrants in Brazilian society. The complexity of the context when it comes to its didactic-pedagogical field relying on transformative practices and social justice; and the need for investigating teachers Education and practice require an autoethnographic perspective. The approximation of PWLg to autoethnography is developed along the whole thesis. PWLg is presented, as well as the discussions about migrant women and their higher vulnerability that strongly influences the learning process, therefore, their integration in society. Emotions emerging from the relation students-teacher and its relation to autoethnography itself are also articulated. Thus, I search for addressing teaching locality and contingency through wider lenses for doing research. The bond with subjectivity is enhanced, by exposing subject/object of research, recognizing and auto investigating my own pedagogical practice and its possible implications for Teachers Education critically. In this sense, data are discussed and presented, thereby the unveiling of dilemmas, frustrations and emotions that contributed for generating high tension as I engaged weekly in the encounters with participants. The tension turning point has given me some reorientations for practice and research in PWLg, thus, transforming them. There are compelling evidences for discussion of interculturality and identities. From the data it is possible to discuss the possibility of an intersectional perspective for helping teachers addressing and dealing with categories of gender and race in their teaching practices. Also, it seems to be paramount for the teachers to be aware of the reasons why migrant women are more vulnerable and to rethink teachers’ practices and education when it comes to gender. Emotions seem to reveal an enriching path for comprehending a more sensitivity to context, aligned to the emotional dimension already considered by PWLg concept. Finally, I defend the implications for teachers’ education considering the teacher as a researcher, moved by affect and availability for critical self-interrogation and more sensible to contexts needs. I expect that this thesis sensitizes teacher for the idiosyncrasies involved in teaching-learning PWLg, which can cause serious dizziness, disestablishing fundamental issues of their professional identities. I also desire that this study may represent one of the possibilities for exploring autoethnography potentialities, by contributing to its productions and meanings in the field of Applied Linguistics in Brazil.
“What is like in your country?” Autoethnographic study of a Portuguese as Welcoming Language pedagogical practice for migrant women in Brasil: implications for teachers education
Keywords: Autoetnografia; Português língua de acolhimento; Mulheres migrantes; Emoções; Formação de professores; Autoethnography; Portuguese welcoming language; Migrant women; Emotions; Teachers education; LINGUISTICA, LETRAS E ARTES::LINGUISTICA